Stepwise Treatment for Abnormally Invasive Placenta with Placenta Previa - Sumigama, Seiji; Kotani, Tomomi; Hayakawa, Hiromi (The Surgery Journal, 2021)
Placenta accreta spectrum (PAS) disorder often causes a large amount of intraoperative bleeding in a short period which makes maternal circulation unstable and threatens life. As a countermeasure, two-stage surgery combined with selective uterine arterial embolization (UAE), named “stepwise treatment” was introduced in 2003. At a cesarean section (CS), only the baby is delivered and the placenta is left in situ. The transcatheter angiographic UAE is performed on the operation day, followed by the total hysterectomy on 5 to 7 days after CS. The difficulty in the operative procedures for hysterectomy and the amount of bleeding can be reduced by the added effect of the blood flow interruption by UAE and the uterine involution. Although there are not many indication cases, this is the prudent operation that should be considered for the most severe PAS case such as total placenta increta/percreta with placenta previa.In this article, the practical procedures and tips of stepwise treatment are described.
Keywords: placenta accreta spectrum; abnormally invasive placenta; placenta previa; modified cesarean hysterectomy; stepwise treatment; uterine arterial embolization; catheter occlusion